2017
DOI: 10.17265/1537-1514/2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of EVA (Economic Value-Added) and Accounting Profit in Explaining Share Returns of Deposit Banks

Abstract: In this study, the success of EVA (Economic Value-Added, a modern performance assessment method) and net profit (a conventional performance assessment method) in explaining the financial performance of corporates was compared. For this purpose, the stock market performance of the shares of deposit banks operating in the banking sector in Turkey was used as the performance indicator of corporates. Then, EVA and the net profit of the period were used to explain the stock market performance of the deposit banks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Using a panel regression model,Boztosun (2017) studied the relationship between the value-based EVA and accounting-based ROE measures by applying the current year and one-year lagged values of the stock returns of banks using data of 8 deposit banks on BIST between the years 2005 and 2016. He concluded that the current and one-year lagged stock returns of banks are explained more strongly by the value-based EVA measure than the accounting-based ROE measure and that EVA can be used in the Turkish banking sector(Boztosun, 2017, p. 575).…”
mentioning
confidence: 99%
“…Using a panel regression model,Boztosun (2017) studied the relationship between the value-based EVA and accounting-based ROE measures by applying the current year and one-year lagged values of the stock returns of banks using data of 8 deposit banks on BIST between the years 2005 and 2016. He concluded that the current and one-year lagged stock returns of banks are explained more strongly by the value-based EVA measure than the accounting-based ROE measure and that EVA can be used in the Turkish banking sector(Boztosun, 2017, p. 575).…”
mentioning
confidence: 99%